PENGARUH LOKASI, TINGKAT SUKU BUNGA, PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN MASYARAKAT DALAM PENGAMBILAN KREDIT (Studi Pada PD. BPR BKK Kota Semarang Cabang Gayamsari) - Kholid Farid (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2019)
The purpose of this research is to analyze the influence of location, interest rates, services and promotion of community decisions in taking credit. The population in this study were all PD credit customers. Semarang City BKK BPR Branch Gayamsari as many as 218 customers (Data As of December 2017). While the samples taken were 70 people. The sampling technique used is Convenience Sampling. The data analysis tool used in this study is multiple regression analysis. Based on the results of the study: There is a significant influence between the location of community decisions in taking credit, There is a significant influence between interest rates on community decisions in taking credit, There is a significant influence between services to community decisions in taking credit, There is a significant influence between promotion of community decisions in taking credit. Simultaneously there is a significant influence between location, interest rates, service and promotion of community decisions in taking credit